Standardising neonatal and paediatric antibiotic clinical trial design and conduct: the PENTA-ID network view - Folgori, L; Lutsar, I; Standing, J; Walker, A; Roilides, E; Zaoutis, T; Jafri, H; Turner, M; Sharland, M (BMJ Journals, 2019)
Background: Antimicrobial development for children remains challenging due to multiple barriers to conducting randomised clinical trials (CTs). There is currently considerable heterogeneity in the design and conduct of paediatric antibiotic studies, hampering comparison and meta-analytic approaches. The board of the European networks for paediatric research at the European Medicines Agency (EnprEMA), in collaboration with the Paediatric European Network for Treatments of AIDS – Infectious Diseases (PENTA-ID) network (www.penta-id.org), recently developed a Working Group (WG) on paediatric antibiotic CT design, involving academic, regulatory and industry representatives. Objectives: The evidence base for any specific criteria for the design and conduct of efficacy and safety antibiotic trials for children is very limited and will evolve over time as further studies are conducted. The suggestions being put forward here are based on the adult EMA guidance, adapted for neonates and children. In particular, this document provides suggested guidance on the general principles of harmonisation between regulatory and strategic trials, including (I) standardised key inclusion/exclusion criteria and widely applicable outcome measures for specific clinical infectious syndromes (CIS) to be used in CTs on efficacy of antibiotic in children; (II) key components of safety that should be reported in paediatric antibiotic CTs; (III) standardised sample sizes for safety studies. Results: Summarising views from a range of key stakeholders, specific criteria for the design and conduct of efficacy and safety antibiotic trials in specific CIS for children have been suggested. Conclusion: The recommended criteria are intended to be applicable to both regulatory and clinical investigator-led strategic trials and could be the basis for harmonisation in the design and conduct of CTs on antibiotics in children. The next step is further discussion internationally with investigators, paediatric clinical trials networks and regulators.